Applied evanescent wave on zinc oxide nanorods coated glass surface for sensing applications / Mohd Hafiz Jali - Mohd Hafiz , Jali (2021)
A simple and workable optical fiber sensor was successfully proposed and demonstrated by integrating the microfiber and the glass surface coated with Zinc Oxide (ZnO) nanorods. It exploited the distinctive features of the large evanescent wave of the microfiber and surface absorption capability of the ZnO nanomaterials coated glass surface to couple with the surrounding analyte. An experimental validation was performed to optimize and verify the sensing performance of the proposed structure. ZnO nanorod growth time of 12-hours and microfiber waist diameter of 6 µm provide optimum sensing results towards the changes of humidity concentration level. The diameter of silica fiber was reduced by tapering process using flame brushing technique and the glass surface was coated with ZnO nanorods using hydrothermal synthesis method. A significant response to humidity concentrations level ranging from 35 %RH to 85 %RH has been observed and the output power of the proposed sensor has decreased linearly from -16.32 dBm to -18.68 dBm with linearity of 95.87 %. The sensitivity and the resolution of the ZnO nanorods coated glass improve by a factor of 2.8 and 7.5 respectively, as compared to the uncoated glass substrate. The proposed sensor also demonstrates a good response to formaldehyde concentrations from 0 ppm to 0.18 ppm. The output power of the proposed sensor has reduced linearly from -22.64 dBm to -24.24 dBm with sensitivity and resolution of 9.78 dBm/ppm and 0.0016 ppm respectively. The sensitivity improves by a factor of 3 and the resolution by a factor of 2.5 when the glass surface is coated as compared to uncoated glass surface. It is due to strong chemisorption process and changeable refractive index of the ZnO nanorods coated glass surface. The proposed sensor successfully employs the interaction between the ZnO nanorods surface and the evanescent field from the microfiber which reduce the striving effort in handling the microfiber during the synthesis process and sensing applications. In addition, the performance of the proposed sensor has been further enhanced by incorporating microsphere resonator with diameter of 234 µm on the ZnO nanorods coated glass surface. For humidity sensing, it produces better sensitivity of 0.0748 dBm/%RH and 0.0142 nm/%RH as compared the straight microfiber laid on the ZnO coated glass substrate with 0.0527 dBm/%RH and 0.0097 nm/%RH respectively. The standard deviation and resolution also improve by a factor of 1.7 and 2.4 respectively as compared to the straight microfiber laid on the ZnO nanorods coated glass. While for the formaldehyde sensor, the sensitivity improves by a factor of 1.84 and 1.33 in terms of output power and wavelength shift respectively as compared to straight microfiber laid on the ZnO coated glass substrate. The resolution also was greatly improved by a factor of 1.87 as compared to straight microfiber laid on the ZnO coated glass substrate. It is due to the ultra-high Q factor of microsphere which enhanced interaction between the whispering gallery mode evanescent components with surrounds analyte.